Análise peptidômica de venenos animais - Breno Rates Azevedo (2011)
The present study aimed at the prospection and characterization of biologically active peptides in venoms of animal representatives of the Brazilian biodiversity, namely Tityus serrulatus (Arachnida, Scorpiones, Buthidae), Acanthoscurria natalensis (Arachnida, Araneae, Theraphosidae) and Phasmahyla jandaia (Anura, Hylidae, Phyllomedusinae). For the attainment of such goal, mass spectrometry was employed as the central tool. The sequencing of new peptidic families or variants from the venom of T. serrulatus and from theskin secretion of P. jandaia, which allowed inferences on the biology of these defensive systems, and the complete determination of the primary structure of the toxin -TRTX-An1a from the venom of A. natalensis are highlighted. Moreover, it has been demonstrated that - TRTX-An1a elicits an increase in the spontaneous discharges frequency and a diminishment in the action potential amplitude in Periplaneta americana DUM neuron preparation.